Power Delivery Network Modeling And Simulation By Using Delaunay-Voronoi Triangulation And The Latency Insertion Method - Chin, Wei Chun (Universiti Sains Malaysia, 2018)
Power integrity of a design plays an important role in affecting the signal integrity and the overall performance of the design. Therefore, the concern of the project is on the performance of power delivery network (PDN) on power plane. The research is focused into the analysis of PDN by modeling and simulation of the power plane. In the project, power plane is modeled using Delaunay-Voronoi algorithm and for simulation, a fast transient simulation algorithm which is latency insertion method (LIM) is applied. However, typical LIM algorithm is facing problem on its stability. Therefore, in the project, modeled power planes are simulated with basic LIM and voltage-in-current formulated LIM. The transient response and direct current (dc) response of the PDN are simulated and discussed and the simulated results from the two algorithms are compared in term of their accuracy and stability. The results has shown the effect of meshing size and shape to the simulated response. For PDN simulation, the results have shown the change in maximum stable time step of basic LIM from 10 ps to 2 ps due to the usage of finer meshing. For improved LIM, the results has shown a stable output over all time steps but with an increase in degradation of accuracy as tabulated in Table 4.4 and 4.5. In overall, basic LIM has shown its strength on the accuracy provided that the simulation is stable while improved LIM has shown its strength on stability but its accuracy degrades with the increase of time step.